Association between Congenital Anomalies and Area-Level Deprivation among Infants in Neonatal Intensive Care Units - Bassil, Kate L.; Collier, Sarah; Mirea, Lucia; Yang, Junmin; Seshia, Mary M.K.; Shah, Prakesh S.; Lee, Shoo K.; null (American Journal of Perinatology, 2013)
Objective To examine the relationship between area-level material deprivation and the risk of congenital anomalies in infants admitted to neonatal intensive care units (NICUs) across Canada.Study Design The Canadian Neonatal Network database was used to identify admitted infants who had congenital anomalies between 2005 and 2009. The association between congenital anomalies and material deprivation quintile was assessed using logistic regression analysis.Results Of 55,961 infants admitted to participating NICUs during the study period, 6002 (10.7%) had major, 6244 (11.2%) had minor, and 43,715 (78.1%) had no anomalies. There were higher odds of major anomalies (odds ratio [OR] 1.13, 95% confidence interval [CI] 1.03 to 1.24) but not minor anomalies (OR 1.01, 95% CI 0.93 to 1.11) in the highest-deprivation areas as compared with the lowest-deprivation area of maternal residence. Analyses of groups of major anomalies revealed higher odds for chromosomal (OR 1.48, 95% CI 1.05 to 2.10) and multiple-systems (OR 1.40, 95% CI 1.14 to 1.71) anomalies in the highest-deprivation areas compared with the lowest-deprivation areas.Conclusion There are socioeconomic inequalities in the risk of major congenital anomalies, especially chromosomal and multiple-systems anomalies, in the NICU population with the highest rates in the most socioeconomically deprived areas.
Keywords: inequalities; socioeconomic; infant; congenital anomaly